2006
DOI: 10.1074/mcp.m500251-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis Provides New Insights into Chilling Stress Responses in Rice

Abstract: Low temperature is one of the major abiotic stresses limiting the productivity and the geographical distribution of many important crops. To gain a better understanding of chilling stress responses in rice (Oryza sativa L. cv. Nipponbare), we carried out a comparative proteomic analysis. Three-week-old rice seedlings were treated at 6°C for 6 or 24 h and then recovered for 24 h. Chilling treatment resulted in stress phenotypes of rolling leaves, increased relative electrolyte leakage, and decreased net photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
372
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(435 citation statements)
references
References 40 publications
56
372
6
1
Order By: Relevance
“…The down-regulation of these key enzymes shows a clear indication that carbon fixation or assimilation is highly disturbed when rice leaves are exposed to heat stress. Similar to our results, photosynthesis-related enzymes such as Rubisco, Rubisco activase, or PRK, have also been identified as down-regulated proteins in several environmental stresses, including heat treatment [5,19,41,42]. Heat-induced changes of Rubisco subunits have also been monitored in heat-sensitive and tolerant rice seedlings and it has been suggested that high temperature (over 407C), for prolonged periods (after 2 h) significantly inhibited the activity and quantity of Rubisco subunits [41].…”
Section: Energy and Metabolismssupporting
confidence: 88%
See 2 more Smart Citations
“…The down-regulation of these key enzymes shows a clear indication that carbon fixation or assimilation is highly disturbed when rice leaves are exposed to heat stress. Similar to our results, photosynthesis-related enzymes such as Rubisco, Rubisco activase, or PRK, have also been identified as down-regulated proteins in several environmental stresses, including heat treatment [5,19,41,42]. Heat-induced changes of Rubisco subunits have also been monitored in heat-sensitive and tolerant rice seedlings and it has been suggested that high temperature (over 407C), for prolonged periods (after 2 h) significantly inhibited the activity and quantity of Rubisco subunits [41].…”
Section: Energy and Metabolismssupporting
confidence: 88%
“…A relative, electrolyte leakage analysis was conducted according to the protocol of Yan et al [19] with some modifications. One gram of leaf disks (1 cm diameter) were placed in 50 mL falcon tubes containing 25 mL of Milli-Q water and incubated at 287C under light for 2 h. The electrical conductivity of the bathing solution (L t ) was measured after 2 h using a conductivity meter (Model 162; Thermo Orion, MA).…”
Section: Relative Ion Leakage and Lipid Peroxidation Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…6). The disparity between mRNA and corresponding protein expressions was not surprising [61], since mRNA expression means the tendency of the corresponding encoded protein which does not always happen due to the posttranscriptional and posttranslational modifications [61,62].…”
Section: Correlation Between Gene Expressions and Protein Abundancesmentioning
confidence: 99%
“…However, the results indicated that mRNA expressions did not correlate well with the protein abundances (data not shown). The disparity between mRNA and corresponding protein expressions was not surprising [49], since mRNA expression means the tendency of the corresponding encoded protein which does not always happen due to the posttranscriptional and posttranslational modifications [49,50].…”
Section: Correlation Between Gene Expressions and Protein Abundancesmentioning
confidence: 99%